2022
DOI: 10.1371/journal.pone.0276216
|View full text |Cite
|
Sign up to set email alerts
|

Association of anthropometric indices with the development of multimorbidity in middle-aged and older adults: A retrospective cohort study

Abstract: Background Previous studies have explored the relationship between body mass index (BMI) and multimorbidity. However, the relationship between other obesity indicators and their dynamic changes and multimorbidity has not been systematically estimated. Therefore, we aimed to investigate the association of BMI and other obesity indicators, including waist circumference (WC), waist-to-height ratio (WHtR), waist divided by height0.5 (WHT.5R), and body roundness index (BRI) and their changes and the risk of multimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Considering this evidence, abdominal obesity indices and body fat percentage indices may offer greater accuracy than BMI in identifying adiposity and, consequently, may provide more precise predictions regarding the onset of multimorbidity. Although waist circumference‐related abdominal obesity indices and hip circumference‐related indices exhibit different associations with chronic diseases, 22 the existing studies only examined the associations between waist circumference‐related indices and incident multimorbidity 23–25 . We did not find any studies examining the effects of hip circumference‐related indices on incident multimorbidity.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Considering this evidence, abdominal obesity indices and body fat percentage indices may offer greater accuracy than BMI in identifying adiposity and, consequently, may provide more precise predictions regarding the onset of multimorbidity. Although waist circumference‐related abdominal obesity indices and hip circumference‐related indices exhibit different associations with chronic diseases, 22 the existing studies only examined the associations between waist circumference‐related indices and incident multimorbidity 23–25 . We did not find any studies examining the effects of hip circumference‐related indices on incident multimorbidity.…”
Section: Introductionmentioning
confidence: 83%
“…Abdominal obesity was found to elevate plasma triglycerides and low-density lipoprotein concentrations, thereby increasing the risk of hyperlipidaemia, insulin resistance and cardiovascular disease. 24 Although no studies have examined the effects of hip circumference-related indices on multimorbidity onset, previous studies have reported inverse associations between hip circumference, height and the risk of diabetes, 34,30 cardiovascular diseases, 35 and mortality. 36 A larger hip circumference indicates greater muscle and fat mass in the gluteofemoral region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies that have examined changes in obesity and multimorbidity have also shown inconsistent results. A study from China indicated that increasing WC was associated with a high risk of multimorbidity, regardless of general obesity status at baseline [ 25 ] while another study from Italy suggested that those who lost weight had a significantly increased risk of multimorbidity than other participants. In other words, the relationship between changes in obesity and multimorbidity remains controversial.…”
Section: Introductionmentioning
confidence: 99%